Perancangan Sistem Pakar Diagnosa Penyakit Meningitis Menggunakan Metode Forward Chaining - asrul asrul (Celebes Computer Science Journal, 2020)
This study aims to design an expert system for diagnosing meningitis using the forward chaining method at Makassar Daya Hospital which seeks to adopt human knowledge to computers, so that computers can solve problems as is usually done by special meningitis experts. This type of research uses the forward chaining method as a tool to detect early suspected meningitis (inflammation of the lining of the brain) and how to prevent it. This system is tested using white-box testing to ensure that the system is free from logical errors and its validity is guaranteed. The product produced from this study is an expert system that can handle patients easily and quickly so that the resulting service is better.